1958
DOI: 10.1111/j.1365-2672.1958.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

METHODS OF ASSESSING THE SPORICIDAL EFFICIENCY OF AN ULTRA‐HIGH‐TEMPERATURE MILK STERILIZING PLANT. III. LABORATORY DETERMINATIONS OF THE HEAT RESISTANCE OF SPORES OF BACILLUS SUBTILIS IN WATER AND IN MILK

Abstract: SUMMARY: Thermal death curves for spores of Bacillus subtilis 786 have been determined in water and in milk. Generally a non‐logarithmic order of death was observed. Numbers of survivors were lower in milk than in water, suggesting that there may be inhibitory factors in UHT sterilized milk which affect the germination and/or subsequent growth of heated spores. The thermal death curves for spores suspended in milk yielded Q10 values of about 30 in the range 110–120°. This is higher than the figures previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1959
1959
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This deactivation may have masked additional repair or may have been a further expression of injury. Observations of repair and deactivation could be influenced by inhibitory compounds in milk (Franklin et al, 1958a(Franklin et al, , 1959Franklin, Williams, and Clegg, 1958b;Higginbottom and Taylor, 1960;Segner, Frazier, and Calbert, 1963); however, no inhibition was observed with B. subtilis A spores in the presence of high concentrations of UHT-treated milk. Therefore, neither repair nor deactivation appeared to be an artifact resulting from inhibitory compounds in milk.…”
Section: Discussionmentioning
confidence: 99%
“…This deactivation may have masked additional repair or may have been a further expression of injury. Observations of repair and deactivation could be influenced by inhibitory compounds in milk (Franklin et al, 1958a(Franklin et al, , 1959Franklin, Williams, and Clegg, 1958b;Higginbottom and Taylor, 1960;Segner, Frazier, and Calbert, 1963); however, no inhibition was observed with B. subtilis A spores in the presence of high concentrations of UHT-treated milk. Therefore, neither repair nor deactivation appeared to be an artifact resulting from inhibitory compounds in milk.…”
Section: Discussionmentioning
confidence: 99%
“…FNA 0 could be found in the literature (Burton et al, 1958;Franklin, Williams, and Clegg, 1958b;Franklin et al, 1959), temperature-survivor X I I I curves may become more meaningful and useful 235 245 255 265 275 with the present trend toward UHT processing TREATMENT TEMPERATURE (F) of milk (Burton, 1959;Speck, 1961;Read, 1964).…”
Section: Methodsmentioning
confidence: 99%
“…These 2 recent studies are in excellent agreement. Franklin et al (1958) found a wide range of Q 10 values for spores of different strains of B. subtilis, ranging from 19-35 (z = 7-8-6-5 °C) for the temperature range 110-120 °C. Shehata & Collins (1972) found z = 89 °C, Q ia = 13-3 for spores of B. coagulans in concentrated milk, and z = 11*3 °C, Q 10 = 7-7 for spores of Clostridium sporogenes: these data were obtained over a very limited temperature range of 1195-125 °C.…”
Section: Bacteriological Changesmentioning
confidence: 98%